1996
DOI: 10.1099/0022-1317-77-12-3025
|View full text |Cite
|
Sign up to set email alerts
|

Low pH-induced pore formation by spike proteins of enveloped viruses

Abstract: Exposure of Aedes albopictus cells infected with Semliki Forest virus (SFV;Togaviridae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…VSV faces the same intriguing question about what is responsible for the dissociation of M protein from RNPs. Unlike influenza virus, VSV lacks an ion channel protein although previous studies have found at low pH spike proteins of enveloped viruses such as VSV, Sindbis virus, and Semliki Forest virus can make the viral envelope permeable to propidium iodide (101,114). Also, cells expressing these proteins on the cell surface show a pH-dependent permeability (101,114).…”
Section: Vsv Entry and Uncoatingmentioning
confidence: 98%
See 4 more Smart Citations
“…VSV faces the same intriguing question about what is responsible for the dissociation of M protein from RNPs. Unlike influenza virus, VSV lacks an ion channel protein although previous studies have found at low pH spike proteins of enveloped viruses such as VSV, Sindbis virus, and Semliki Forest virus can make the viral envelope permeable to propidium iodide (101,114). Also, cells expressing these proteins on the cell surface show a pH-dependent permeability (101,114).…”
Section: Vsv Entry and Uncoatingmentioning
confidence: 98%
“…This was an interesting result since influenza virus uses the M2 ion channel protein for acidification of the virion interior (110,169) and our results suggested that VSV uses a different method to accomplish a similar feat with its G protein. Previous studies have found spike proteins of several different enveloped viruses including VSV, Sindbis Virus (SIN), Semliki Forest virus (SFV), influenza HA, and Ebola virus GP2 when exposed to acidic pH, can increase membrane permeability when cells expressing these proteins on the cell surface are exposed to low pH (76,101,112,182). The SFV spike protein's involvement in membrane disruption at low pH was extensively studied with cell permeabilization assays, whole-cell patch-clamp recordings, and dual voltage-clamp intracellular current flow monitoring (112,113,115) and was predicted to be due to pore formation by the E 1 -E 2 -E 3 protein trimers that make up the SFV spike (114).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations